Analisis Faktor-Faktor Yang Mempengaruhi Produksi Usahatani Padi Semi Organik Di Desa Pangkal Mas Jaya Kecamatan Mesuji Timur Kabupaten Mesuji - I Wayan Ryan Anggara; Sutarni; Sri Handayani; Fitriani (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
Semi-organic farming in Pangkal Mas Jaya Village has been carried out since 2019 until now, which fluctuates every year. The purpose of this study was to analyze the income of semi- organic rice production in Pangkal Mas Jaya Village, Mesuji Timur District, Mesuji Regency, to analyze the factors that influence semi-organic rice production in Pangkal Mas Jaya Village, Mesuji Timur District, Mesuji Regency, and to analyze the business scale of semi-organic rice production. organic matter in Pangkal Mas Jaya Village, East Mesuji District, Mesuji Regency. This research was conducted in Pangkal Mas Jaya Village, Mesuji Timur District, Mesuji Regency in May 2022. The population in this study were farmers who did rice farming with a sample of 32 respondents. The analytical method used is quantitative analysis (regression analysis, Douglas Cobb function and statistical tests) and qualitative analysis (descriptive). The results of the study regarding the average amount of income from semi-organic rice farming is Rp. 35,178,333.33, namely the total costs incurred in semi-organic rice farming are an average of Rp. 13,355,247.00, and an average profit of Rp. .21,823,086.00, with an R/C value of 2.63 and a B/C value of 1.63. Production factors that have a significant effect on semi-organic rice production are labor (X1), land area (X2), organic fertilizer (X3), and seeds (X5) while organic pesticides (X4) do not have a significant effect on rice production semi organic. Semi-organic rice farming activities are at the level of increasing business scale (increasing return to scale), which means that if the use of production factors is added, it will produce additional production with a larger proportion.